Mitochondrial genome of two marine fungal species. (1st November 2016) - Konovalova, Olga; Logacheva, Maria
Abstract: Here is a first record for a mitochondrial genome of marine fungus Acremonium fuci and closely related species Emericellopsis sp. One strain for each species, differentiated by morphological features was studied. Complete mitochondrial sequences are 24 565 and 24 951 bp in length. The circular molecule encodes all genes typical for fungal mitochondrial genomes: 15 protein-coding genes, 28 tRNAs, and large and small subunits of RNA. All structural genes are located on one strand and transcribed in one direction. Mitogenomes of species have 99% identity in protein-coding genes, but differ in some structural features: one of them has additional ORF with a similarity to cox1 gene, and another one has an intron in nad5 gene.